Integrating SPOCs in Software Testing Education: Evidence in Emergency Remote Courses - Prates, Jorge Marques (2023)
Nowadays, SPOCs (Small Private Online Courses) have been used as complementary methods to support classroom teaching. SPOCs are courses that apply the usage of MOOCs (Massive Open Online Courses), combining classroom with online education, making them an exciting alternative for contexts such as emergency remote teaching. Although SPOCs have been continuously proposed in the software engineering teaching area, it is crucial to assess their practical applicability via measuring the effectiveness of this resource in the teaching-learning process. In this context, this paper aims to present an experimental evaluation to investigate the applicability of a SPOC in a Verification, Validation, and Software Testing course taught during the period of emergency remote education during the COVID-19 pandemic in Brazil. Therefore, we conducted a controlled experiment comparing alternative teaching through the application of a SPOC with teaching carried out via lectures. The comparison between the teaching methods is made by analyzing the students’ performance during the solving of practical activities and essay questions on the content covered. In addition, we used questionnaires to analyze students’ motivation during the course. Study results indicate an improvement in both motivation and performance of students participating in SPOC, which corroborates its applicability to the software testing teaching area.